2021
DOI: 10.21203/rs.3.rs-403040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wax-Oil Lubricants to Reduce the Shear Between Skin and PPE

Abstract: Prolonged use of tight-fitting PPE, e.g., by COVID-19 healthcare workers leads to skin injuries. An important contributor is the shear exerted on the skin due to static friction at the skin-PPE interface. This study aims to develop an optimised wax-oil lubricant that reduces the friction, or shear, in the skin-PPE contact for up to four hours. Lubricants with different wax-oil combinations were prepared using beeswax, paraffin wax, olive oil, and mineral oil. In-vivo friction measurements involving seven parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Therefore, the microbial distribution characteristics on the skin of persons wearing PPE may be different from that of people working in a normal environment. Previous studies 17 have shown that wearing personal protective equipment can induce skin damage such as erythema, pruritus, erosion, and ulceration among others. However, there is no research on the effect of wearing personal protective equipment on the skin surface microorganisms of the health workers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microbial distribution characteristics on the skin of persons wearing PPE may be different from that of people working in a normal environment. Previous studies 17 have shown that wearing personal protective equipment can induce skin damage such as erythema, pruritus, erosion, and ulceration among others. However, there is no research on the effect of wearing personal protective equipment on the skin surface microorganisms of the health workers.…”
Section: Introductionmentioning
confidence: 99%